Pope Francis, Priesthood and Mission. Ten Inspirational Insights - Kroeger, James (Annales Missiologici Posnanienses, 2016)
Employing ten representative themes emerging from the speeches and writings of Pope Francis, this medium-length presentation explores the rich treasures of the Pope’s insights on the topic of priesthood and priestly ministry. Twenty-four of his most relevant documents ranging from 2013 to 2016 are quoted directly; additional background material is also provided. The engaging vision of Pope Franciscus is eminently practical, grounded in pastoral realities, profoundly spiritual, and filled with missionary dynamism. For Pope Francis, priests must have “a passion for Jesus and a passion for His people” (Evangelii Gaudium 268).